Consumption values, attitudes towards technology and moderating effects of cultural perspective on mobile phone replacement behaviour among Y generation - Yong, Hiew Wei (2017)
Frequent change of mobile phones is believed to bring negative consequences to our well-being. The replacement behaviors are influenced by complex reasoning that lies beyond product depreciation such as consumption values and technology adoption. The main objective of this study was to examine the factors associated with the tendency of consumers' compulsive replacement behavior on a mobile phone. The Theory of Consumption Values, Technology Acceptance Model and Theory of Planned Behavior were applied as the basis for the theoretical framework of the study. These theories serve to guide the conceptual framework which includes the study of consumption values (functional values, epistemic values, emotional values and social values) and attitude towards technology and tendency of consumers' compulsive replacement behavior. This study also investigates the moderation effect of cultural perspectives on the relationship between consumption values and attitudes towards technology and tendency of compulsive replacement behavior. The conceptualized model was then developed into replacer typologies. A multi-stage sampling method was used and the sample comprising of 500 consumers were obtained from Mid Valley Megamall, Berjaya Times Square Shopping Centre, Kuala Lumpur Convention Centre and Cheras Leisure Mall. The data obtained in this study was collected via self-administered questionnaire. The data was statistically analyzed using descriptive analysis, structural equation modeling, cluster analysis and chisquare analysis. Results indicated that most of the respondents had low to moderate level of compulsive replacement behavior tendency. Results also suggested that there was a significant relationship between epistemic value, emotional value and social value and attitude towards technology. Meanwhile, findings showed that there were some forms of moderation effects of cultural perspective on the relationship between consumption values, attitude towards technology and tendency of compulsive replacement behavior. In addition, the variables of function value, epistemic value, emotional value and social value were identified as the statistically significant predictors of compulsive replacement behavior tendency. Based on the confirmed hypothesized model, replacer typologies which consisted of apathetic replacers, pragmatic replacers and enthusiastic replacers were constructed. Majority of the respondents fell under pragmatic and apathetic replacer group. The results from chisquare analysis showed that enthusiastic replacers have a greater emphasis on the consumption values, are highly motivated towards new technology, have high incomes and are likely to have the tendency of compulsive in replacement of mobile phones. This study appeared to support the relationship consumption values and consumers’ tendency of compulsive mobile phone replacement behavior. Further studies should explore about other factors that influence tendency of compulsive mobile phone replacement behavior with a diversified range of population or qualitative research method.